Endothelins in cardiovascular biology and therapeutics - Dhaun, Neeraj; Webb, David J (Nature reviews cardiology, 2019)
Cardiovascular disease is a major contributor to global morbidity and mortality and is the common end point of many chronic diseases. The endothelins comprise three structurally similar peptides of 21 amino acids in length. Endothelin 1 (ET-1) and ET-2 activate two G protein-coupled receptors - endothelin receptor type A (ET ) and endothelin receptor type B (ET ) - with equal affinity, whereas ET-3 has a lower affinity for ET . ET-1 is the most potent vasoconstrictor in the human cardiovascular system and has remarkably long-lasting actions. ET-1 contributes to vasoconstriction, vascular and cardiac hypertrophy, inflammation, and to the development and progression of cardiovascular disease. Endothelin receptor antagonists have revolutionized the treatment of pulmonary arterial hypertension. Clinical trials continue to explore new applications of endothelin receptor antagonists, particularly in treatment-resistant hypertension, chronic kidney disease and patients receiving antiangiogenic therapies. Translational studies have identified important roles for the endothelin isoforms and new therapeutic targets during development, in fluid-electrolyte homeostasis, and in cardiovascular and neuronal function. Novel pharmacological strategies are emerging in the form of small-molecule epigenetic modulators, biologics (such as monoclonal antibodies for ET ) and possibly signalling pathway-biased agonists and antagonists.